Emotional Processes in Juvenile Delinquents: Criminological Implications - Pavlović, Svetlana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2024)
Juvenile delinquency represents a serious societal issue, and this paper focuses on the emotional aspects associated with it. Juvenile offences are estimated to account for 7% of all criminal acts worldwide, with significant social consequences. Delinquents often come from dysfunctional families, abuse psychoactive substances, and experience psychiatric disorders, highlighting the complexity of this problem. The paper’s emphasis is on the emotional processes underlying delinquency, starting with emotional intelligence (EI). Research indicates a connection between low EI and juvenile delinquency, highlighting the role of emotion recognition and emotional regulation in this context. Various forms of delinquency may be linked to different aspects of emotional regulation, particularly impulsivity. The paper also considers psychopathy as a prominent personality characteristic closely related to juvenile delinquency, exploring the emotions that describe psychopathy. Factors such as manipulativeness, low empathy, and impulsivity are often present in juveniles with psychopathic traits. Additionally, in this paper, we are interested in Callous-Unemotional (CU) Taits. The CU model is applied to describe the psychopathic tendencies of children and adolescents. The connection between emotions and cognition in the context of juvenile delinquency is illustrated through findings that discuss two dimensions of empathy: affective and cognitive, as well as the role of executive functions in delinquent behaviors. Finally, the importance of research seeking to explain the link between emotions and cognition is emphasized, particularly in the context of understanding personality traits responsible for such behaviors, such as psychopathy.